Light and electron microscopic examination of pineal gland in rats exposed to constant light and constant darkness - Kus, I; Sarsilmaz, M; Ozen, OA; Turkoglu, AO; Pekmez, H; Songur, A; Kelestimur, H (Maghira & Maas Publications, 2004)
OBJECTIVE: This study was aimed to examine the pineal gland of rats exposed to constant light and darkness at light and electron microscopic level. DESIGN: For this purpose 18 male Wistar rats were used. Animals were divided into three groups. Rats in group I (Control) were kept under 12 hrs light: 12 hrs dark conditions. Rats in group 11 were exposed to constant darkness, while rats in group III were exposed to constant light for 6 weeks. At the end of the experiment, all animals were killed by decapitation. The pineal glands of rats were removed, then processed for light and electron microscopy RESULTS: In our study, extensive number of pinealocytes was observed in the structure of pineal gland of rats exposed to constant darkness and some of the observed pinealocytes were determined to contain double nucleoli. Furthermore, mitochondria and lipid droplets in the cytoplasm of pinealocytes were increased and rough endoplasmic reticulum sacs were enlarged in this group. Whereas, in rats those exposed to the constant light, a decrease in pinealocyte intensity was associated with increase in the connective tissue between parenchymal cells. Additionally, mitochondria and lipid droplets in the cytoplasm of cells were decreased. CONCLUSIONS: It was observed that the pinealocyte cell activity of rats exposed to constant darkness was increased but decreased in rats exposed to constant light.
Keywords: light; darkness; pineal gland; rat; light and electron microscopy